2022
DOI: 10.3390/ijms23116054
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Gene and miRNA Expression in Cervical Intraepithelial Neoplasia and Cervical Cancer

Abstract: Cervical cancer is one of the most common malignancies in women in terms of prevalence and mortality. Cervical cancer has some particularities that distinguish it from any other oncologic pathology: first, it is completely preventable by prompt detection of its precursor, cervical intraepithelial neoplasia (CIN); second, the Human Papillomavirus (HPV) infection is a known etiological agent; third, the mean age at diagnosis is much lower than in other oncologic conditions, as a consequence of the sexually-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The decreased expression of miR-205-5p was observed in both CIN and cancer samples compared to normal samples, which may serve as an early biomarker in the diagnosis of premalignant cervical lesions. 25 Through miR-205-5p inhibitor or mimic transfection and dual luciferase reporter assays, we confirmed that ESM1 is a target of ESM1 in cervical cancer.…”
Section: Discussionsupporting
confidence: 53%
“…The decreased expression of miR-205-5p was observed in both CIN and cancer samples compared to normal samples, which may serve as an early biomarker in the diagnosis of premalignant cervical lesions. 25 Through miR-205-5p inhibitor or mimic transfection and dual luciferase reporter assays, we confirmed that ESM1 is a target of ESM1 in cervical cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Reduced protein expression of TIMP-3 was associated with reduced tumor differentiation and increased metastatic activity, since its binding to MMPs in tumor cells is leading to a reduced ECM-degrading activity ( 38 ). Moreover, a decreased expression of TIMP-3 has been reported in cervical intraepithelial neoplasia and cervical cancer related to HPV, which in turn may be responsible implicitly by an impaired extracellular matrix degradation activity and cyto-architectural abnormalities ( 39 ). In our study, in fibropapillomas, a weak to moderate expression was noted by immunohistochemistry mostly in the upper epithelial layers, and next, by western blot analysis, a down-regulated expression was confirmed, which may support an important contribution in impairing the collagenases activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that the expression level of TIMP3 is lower in cervical intraepithelial neoplasia and cancer tissues than in normal samples [ 131 , 132 , 133 , 134 ] ( Table 4 ). According to the TCGA data, TIMP3 expression is lower in cancer samples than in normal samples [ 131 ].…”
Section: Timp3 In Gynaecological Cancersmentioning
confidence: 99%
“…Some studies have indicated that the expression level of TIMP3 is lower in cervical intraepithelial neoplasia and cancer tissues than in normal samples [ 131 , 132 , 133 , 134 ] ( Table 4 ). According to the TCGA data, TIMP3 expression is lower in cancer samples than in normal samples [ 131 ]. Compared to patients with lower expression levels of TIMP3 in cervical cancer tissues, those with higher TIMP3 expression correlate with a lower survival rate; however, no significance has been observed [ 131 ].…”
Section: Timp3 In Gynaecological Cancersmentioning
confidence: 99%
See 1 more Smart Citation